Forced migration in sub-Saharan Africa: some subsidies on refugees in Mozambique - Patrício, Gonçalves Valzim (2018)
In this article we intend to make a succinct analysis of the forced migratory dynamics in sub-Saharan Africa that affect Mozambique, a country inserted in a complex regional context that refers to the plural condition of a country of emigration, immigration and transit. The findings of the investigation indicate that forced migratory flows in the country come mainly from central Africa and the Horn of Africa, as a result of the trivialized and persistent violence in the countries of these regions. Refugees seeking settlement or asylum mainly go to central and northern Mozambique, as a result of the relatively stable socio-economic and political situation they find, when compared to many countries in the sub-Saharan region.